Studies on fluctuating asymmetry (FA) for certain morphological traits in four species of the Drosophila bipectinata complex - Banerjee Parul (Genetika, 2015)
Fluctuating asymmetry (FA) is defined as subtle deviations from perfect bilateral symmetry, evident in differences between the right and the left sides of any given trait. It is a pattern of variation between sides and measures developmental instability. Differences in the level of FA may be used for comparing developmental precision among closely related species and thus may give an idea whether developmental stability was affected during the divergence and separation of populations into distinct species. Keeping this in view, FA was studied in four species of the Drosophila bipectinata complex i.e. D. bipectinata, D. parabipectinata, D. malerkotliana and D. pseudoananassae. In females of all the four species, FA values did not vary significantly for any of the traits considered. However, in case of males, they varied significantly for Wing length (WL) and sex comb tooth number (SCTN). Also, while in females Composite fluctuating asymmetry (CFA) did not exhibit significant variation, in males it was found to vary significantly across the four species. However, Bonferroni t-tests did not reveal any consistent difference in FA levels between any two species. The magnitude of FA was found to differ significantly among traits and CFA values were found to be higher for males than females in all the four species. Therefore, it may be concluded that the level of FA shows trait specific variations and males are more prone to developmental perturbations. However, the FA levels are more or less similar in all the four species of this complex. Thus, developmental precision remains nearly same in all the four species of this complex irrespective of the degree of evolutionary divergence reached.